Access to rehabilitation for patients with stroke in Australia. Issue 1 (23rd November 2018) - Lynch, Elizabeth A; Mackintosh, Shylie; Luker, Julie A; Hillier, Susan L
Abstract: Objective: To identify factors associated with receiving acute goal‐directed treatment, being assessed for ongoing rehabilitation, and receiving post‐acute rehabilitation after having a stroke. Design: Retrospective analysis of National Stroke Audit data for patients with acute stroke treated at Australian hospitals during 1 September 2014 – 28 February 2015. Setting, participants: 112 Australian hospitals that admit adults with acute stroke. Main outcomes: Associations between patient‐related and organisational factors and the provision of rehabilitation interventions. Results: Data for 3462 patients were eligible for analysis; their median age was 74 years, 1962 (57%) were men, and 2470 (71%) had received care in a stroke unit. 2505 patients (72%) received goal‐directed treatment during their acute admission; it was not provided to 364 patients (10.5%) who were responsive, had not fully recovered, and did not refuse treatment. Factors associated with higher odds of receiving goal‐directed treatment included goal‐setting with the patient and their family (odds ratio [OR], 6.75; 95% CI, 5.07–8.90) and receiving care in a stroke unit (OR, 2.08; 95% CI, 1.61–2.70). 1358 patients (39%) underwent further rehabilitation after discharge from acute care; factors associated with receiving post‐acute rehabilitation included care in a stroke unit (OR, 1.73; 95% CI, 1.34–2.22) and having an arm or speech deficit. Dementia was associated with lower odds of receiving acute goal‐directed treatment (OR, 0.49; 95%, 0.33–0.73) and post‐acute rehabilitation (OR, 0.43; 95%, 0.30–0.61). Conclusions: Access to stroke units and to early and ongoing rehabilitation for patients after stroke can be improved in Australia, both to optimise outcomes and to reduce the burden of care on underresourced community and primary care providers.